COMPARISON OF STRAIN ELASTOGRAPHY AND SHEAR WAVE ELASTOGRAPHY FOR DIFFERENTIATING MALIGNANT FROM BENIGN BREAST MASSES - JAMAL, Y; NIGHAT, S; IRUM, R; KHAN, MM; SHEIKH, R (Biological and Clinical Sciences Research Journal, 2022)
To compare the diagnostic performance of shear wave and strain elastography in distinguishing benign and malignant breast lesions. A prospective study carried out from 20th March 2020 to 20th March 2021 at department of Radiology of Sahiwal, Multan, Lahore. The study included women who were lined for surgical excision or core needle biopsy and were examined using B-mode ultrasound and shear and strain wave elastography. A total of 30 female patients with 40 breast lesions were included in the study. Lesions were categorized on B-mode ultrasound as 3 BI-RADS 3, 18 BI-RADS 4A, 5 BI-RADS 4B, 7 BI-RADS 4C, and 7 BI-RADS 5. After performing a B-mode Ultrasound examination, US elastography was done. A 14-MHz transducer was used to obtain high-resolution images. For comparing the diagnostic performance of both, an area under the ROI curve (AUC) from data sets of shear and strain wave elastography was compared. The McNemar test was used for the comparison of sensitivity and specificity of both data sets. Mean age of the participants was 48.4 years (21-80years). 24 out of 40 lesions were benign while 16 were malignant. B mode US imaging showed the diameter of the lesion ranged from 0.5 to 5.2 cm. There was no significant difference between specificity and sensitivity of elastographic images. 6 breast masses showed discrepant results. After category 4a BI-RADs were selectively downgraded on the bases of cutoff values, AUCs showed improvement. Diagnostic performance of shear wave and strain elastography in distinguishing malignant and benign lesions is the same. Combining both has better diagnostic performance than using each individually.